Darkness controlled light switch / Mohd Rozi Jusoh and Mohd Safarin Mohd Samian - Jusoh, Mohd Rozi; Mohd Samian, Mohd Safarin (2000)
Darkness controlled light switch is a circuit that used to ON and OFF the switch automatically depend on the light. Generally, this circuit is used in the street light, at the building light and also in the light at the garden where it can ON and OFF automatically. This project circuit use a basic electronic devices such as integrated circuit , light dependent resistance, relay, transistors, diodes and resistance. This circuit need to connect to lamp where A C supply to the lighting load is thus connected via the contact of the relay. The main futures of this project is to switch ON and OFF the street light automatically without human control. So, we can save the time and electricity for this application. As a result, Darkness Controlled Light Switch is useful for tire future application such as to control street light, building light or the others equipment.